Circulating Natural Autoantibodies to HER2-Derived Peptides Performed Antitumor Effects on Oral Squamous Cell Carcinoma - Liu, Xiu; He, Ziyi; Qu, Yi; Meng, Qingyong; Qin, Lizheng; Hu, Ying (Frontiers in Pharmacology, 2021)
Natural autoantibodies play a crucial role in destruction of malignant tumors due to immune surveillance function. Epidermal growth factor receptor 2 (HER2) has been found to be highly expressed in a variety of epithelial tumors including oral squamous cell carcinoma (OSCC). The present study was thus undertaken to investigate the effect of anti-HER2 natural autoantibodies on OSCC. Compared with cancer-adjacent tissues, cancer tissues from OSCC patients exhibited higher HER2 expression especially in those with middle & advanced stage OSCC. Plasma anti-HER2 IgG levels examined with an enzyme-linked immunosorbent assay (ELISA) developed in-house showed differences between control subjects, individuals with oral benign tumor and patients with OSCC. In addition, anti-HER2 IgG-abundant plasma was screened from healthy donors to treat OSCC cells and to prepare for anti-HER2 intravenous immunoglobulin (IVIg). Both anti-HER2 IgG-abundant plasma and anti-HER2 IVIg could significantly inhibit proliferation and invasion of OSCC cells by inducing the apoptosis, and also regulate apoptosis-associated factors and epithelial-mesenchymal transition (EMT), respectively. Besides, the complement-dependent cytotoxicity (CDC) pathway was likely to contribute to the anti-HER2 IgG mediated inhibition of OSCC cells. After the HER2 gene was knocked down with HER2-specific siRNAs, the inhibitory effects on OSCC cell proliferation and apoptotic induction faded away. In conclusion, human plasma IgG or IVIg against HER2 may be a promising agent for anti-OSCC therapy.